Prognostic factors in Bochdalek hernia - Saraç, Mehmet; Tartar, Tugay; Bakal, Ünal; Aydin, Mustafa; Akdeniz, Ibrahim; Taşkin, Erdal; Kazez, Ahmet (Logos Medical Publishing, 2019)
Objective: In this study, it was aimed to investigate the factors affecting the mortality of newborn infants who underwent surgery due to Bochdalek hernia. Material and Methods: The files of 36 cases with Bochdalek hernia who underwent surgery between 2001 and 2016 were retrospectively reviewed. Results: Two of the patients were twins. The male to female ratio was 19/17. Median gestational age of the patients was 36 (32-38) weeks, maternal age 29 (16-41) years, mean birth weight 3000±503 g, median age at surgery 4 (1-10) days and duration of mechanical ventilation was 8.5 (2-60) days. The mortality rate in our series was 25%. The mortality rate (50%) in patients with gestational age ?36 weeks was significantly higher than the mortality rate (17.8%) in patients with gestational age >36 weeks (p=0.046). The mortality rate (47.1%) of the patients followed up in the neonatal intensive care unit was significantly higher than the mortality rate (5.2% )those monitored in the intensive care unit of the pediatric surgery department (p=0.005). Mortality rates were 43% in cases with prenatal diagnosis, 30% in cases with 5th min. Apgar scores of ?5 and 11% in cases with 5th min. Apgar scores of >5, and 62.9% in cases with pulmonary hypertension. None of the right Bochdalek hernia cases died. Major congenital cardiac anomalies were present in 77.7% of exited patients. Pulmonary vasodilator agents and high frequency mechanical ventilation mode were more commonly used in exited cases. Conclusion: The cases with Bochdalek hernia have a mortality rate of 25 percent. Pulmonary hypertension, prematurity and low birth weight are factors affecting mortality. © 2019 Logos Medical Publishing. All Rights Reserved.
Bochdalek hernisinde prognostik faktörler
Keywords: Bochdalek hernia; Mortality; Prognostic factors; Surgical treatment